2014
DOI: 10.1115/1.4028564
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Fully Developed Opposing Mixed Convection Flow in an Inclined Channel Filled by a Nanofluid

Abstract: In this paper, an analysis is made on the convective heat transfer of a nanofluid between two inclined parallel plates with a uniform heat flux boundary condition. The analytical solutions are obtained explicitly for the velocity, temperature, and pressure distributions, which are dependent on two parameters P 1 and P 2 . By alerting their values, four different regimes for flow reversal are found. On the other hand, it is found that the nanoparticle volume fraction / has a significant influence on the flow re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Differentiating Equation ( 7) with Y and Equation (8) with X respectively, and taking into account (12), then equating them, we obtain…”
Section: Properties Nanofluidmentioning
confidence: 99%
See 1 more Smart Citation
“…Differentiating Equation ( 7) with Y and Equation (8) with X respectively, and taking into account (12), then equating them, we obtain…”
Section: Properties Nanofluidmentioning
confidence: 99%
“…Cimpean [ 11 ] studied the steady fully developed mixed convection flow of a nanofluid in a channel filled with a porous medium. You et al [ 12 ] presented analysis of fully developed opposing mixed convection flow in an inclined channel filled by a nanofluid. Goyal et al [ 13 ] examined numerically natural convective boundary layer flow of a nanofluid past a heated inclined plate in the presence of magnetic field and found that the thermal boundary layer thickness increased with strengthening the value of inclination angle parameter.…”
Section: Introductionmentioning
confidence: 99%
“…Of fundamental importance in engineering and its application, the Nusselt number, skin friction, volume flow rate, and heat carried out by the fluid can be expressed, respectively, as: Nu=2qwLkfΔT;Cf=τwρfU02;Mf=0Lufalse(yfalse)dy;Qf=0Lufalse(yfalse)Tfalse(yfalse)dywhere qw=±knfdTdyy=0,L is the wall heat flux and τw=±μnfdudyy=0,L is the wall shear stress. Thus, using Equation and the wall heat flux and wall shear stress, the Nusselt number, skin friction, volume flow rate, and heat carried out by the fluid can be defined as: Nu=±2A3dθdYY=0,1;ReCf=±A12dUdYY=0,1;Mf=01UdY;Qf=01UθdY.…”
Section: Mathematical Formulationmentioning
confidence: 99%
“…The result of the study highlights that the Knudsen number causes a reduction in velocity and rate of heat transfer whereas the angle of inclination maximizes the friction coefficient and Nusselt number. You et al 17 involved themselves in examining the flow of TiO 2 –H 2 O nanoliquid. The result tells that the volume fraction of nanoparticles significantly affects the declining nature of flow reversal.…”
Section: Introductionmentioning
confidence: 99%